'But I don't know if I want to talk to you': strategies to foster conversational receptiveness across the United States' political divide. Issue 1 (2nd January 2023) - Oliver-Blackburn, Bailey M.; Chatham-Carpenter, April
ABSTRACT: This study explores the conversational receptiveness strategies that are intentionally embedded in the Braver Angels organization's Red/Blue Workshops. These workshops facilitate difficult conversations across the political divide in the United States, especially communication between Republicans and Democrats. Workshop training materials and workshop recordings were analyzed to identify how moderators were trained to encourage conversational receptiveness through structured dialogue. Results identified trained facilitator strategies (greeting behaviors, acknowledging power differences, setting up structures for safety of outgroup conversations, active listening, and showing appreciation for participant input), structured conversational receptiveness practices (limiting assumptions through perspective-taking and locating shared interests), and the strategic sequencing of training activities all contributed to creating dialogic moments. The conversational work done in these workshops around sharing one's own perspective and invoking the perspectives of others, holds potential implications for helping to create communities of dialogue where people can develop conversational receptiveness, both within these workshops and beyond.